Copper-Catalyzed Asymmetric Conjugate Addition to α-Alkylidene Cycloalkanones - Garcia, Pierre; Germain, Nicolas; Woodward, Simon; Alexakis, Alexandre (Synlett, 2015)
The asymmetric copper-catalyzed conjugate addition to α-alkylidene cycloalkanones, substituted at their terminal position with aromatic and aliphatic groups, is reported. While high enantioselectivity is reached using chiral phosphoramidite ligands, with R3Al reagents, moderate diastereoselectivity was observed upon hydrolysis of the aluminium enolates. A Grignard reagent also react with high diastereoselectivity.
Keywords: α-alkylidene cycloalkanones; conjugate addition; copper; trialkylaluminium reagents; Grignard reagents